Respuesta :

Answer:

Step-by-step explanation:

x-y=11

2x+y=19

---------------

x=y+11

2(y+11)+y=19

2y+22+y=19

3y+22=19

3y=19-22

3y=-3

y=-3/3

y=-1

x-(-1)=11

x+1=11

x=11-1

x=10

Answer: x=10, y=-1. (10, -1).

-----------------------------------------

-6x+5y=1

6x+4y=-10

-------------------

9y=-9

y=-9/9

y=-1

6x+4(-1)=-10

6x-4=-10

6x=-10+4

6x=-6

x=-6/6

x=-1

Answer: x=-1, y=-1. (-1, -1).

------------------------------------

2x+9y=25

-4x-9y=-23

-------------------

-2x=2

x=2/-2

x=-1

2(-1)+9y=25

-2+9y=25

9y=25-(-2)

9y=25+2

9y=27

y=27/9

y=3

Answer: x=-1, y=3. (-1, 3).

Answer:

x = 10    y = -1

x = − 13/5    y = 7/5

x = -1     y = 3

Step-by-step explanation: